Molecular Analysis of a Family With Congenital Adrenal Hyperplasia - Genotype/Phenotype Discrepancy - Anastasovska, V; Kocova, M (Walter de Gruyter GmbH, 2007)
Molecular Analysis of a Family With Congenital Adrenal Hyperplasia - Genotype/Phenotype DiscrepancyCongenital adrenal hyperplasia (CAH) is a common autosomal recessive disease with a variable clinical presentation caused by a spectrum of different mutations. A significant association of genotype with phenotype has been reported.The molecular analysis of a girl with a mild form of CAH presenting with precocious pubarche, confirmed that she was heterozygous for two mutations of the CYP21 gene (exon 1, codon 30/exon 8, codon 318). Her mother was homozygous for the codon 30 mutation and her father was homozygous for the codon 318 mutation. The only anomaly in the parents was a difficulty in conceiving. The molecular analysis of this family confirmed the variability of presentation in carriers of different mutations, which caused difficulties in decisions about the timing of therapy and in genetic counseling.